RESORT PANTAI GEDAMBAAN KABUPATEN KOTABARU - Ady Saputra, Muhammad Reza; Andini, Dila Nadya (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2020)
The beach is a very interesting tourist attraction. Coastal tourism is one of the characteristics possessed by the Kotabaru Regency. Gedambaan Beach is a tourist attraction located in Sarang Tiung Village, Pulau Laut Timur District, Kotabaru Regency. The beautiful natural potential is certainly an attraction for tourists to visit Gedambaan Beach. To attract more tourists, it must be supported by adequate infrastructure, one of which is a resort. The resort is needed to support the increase in visitor growth in Gedambaan Beach where the resort's long visit by tourists will affect local income which will indirectly improve the economy in the surrounding area. The problem of designing the Gedambaan Beach resort is how to design a resort that develops the potential of the region by forming a character based on the concept of contextual architecture in the Gedambaan Beach Resort area. To solve the problem, the Harmony Contextual Method is used. This method emphasizes the design by utilizing the natural potential that is applied to the design aspects of the characteristics, environment, and cultural approach to the design of this resort.